2022
DOI: 10.1186/s41935-022-00290-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, perception, attitude, and use of performance-enhancing substances among students of Faculty of Medicine, Alexandria University, Egypt: a pilot study

Abstract: Background The market for performance enhancement substances (PESs) is currently one of the fastest expanding sectors. Most studies have always concentrated on athletes in terms of PESs’ misuse, ignoring a critical segment of the community: the future health-care workers. Thus, the aim of the study was to probe the knowledge, perception, and attitude of medical students regarding the misuse of PESs in sports and medical academic study. A cross-sectional study was conducted among students of Ale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Similar to this result, a study conducted in Kenya on the students of physical education and sports sciences also indicated that due to higher desire of increasing sports performance during competition, students were eager to use these prohibited substances (Rintaugu & Mwangi, 2021). Another study conducted on medical students of Egyptian university also stated that the impulsive attitude of students to win a competition at any cost was one the reasons of their positive attitude towards the use of banned substances (Badr el Dine & Attia, 2022). This attitude emphasizes the significance of promoting fair play among the overall population.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Similar to this result, a study conducted in Kenya on the students of physical education and sports sciences also indicated that due to higher desire of increasing sports performance during competition, students were eager to use these prohibited substances (Rintaugu & Mwangi, 2021). Another study conducted on medical students of Egyptian university also stated that the impulsive attitude of students to win a competition at any cost was one the reasons of their positive attitude towards the use of banned substances (Badr el Dine & Attia, 2022). This attitude emphasizes the significance of promoting fair play among the overall population.…”
Section: Discussionsupporting
confidence: 53%
“…The medical literature has frequently documented instances of steroid use among adolescents (Boyack et al, 2005) The prevalence of energy drink consumption has increased significantly, particularly among adolescents. This age range is specifically targeted as younger people tend to be more attuned to global trends (Badr el Dine & Attia, 2022).…”
Section: Research Paper Knowledge Awareness and Attitudes Towards Dop...mentioning
confidence: 99%
See 1 more Smart Citation